The biological oceanography of the East Australian Current and surrounding waters in relation to tuna and billfish catches off eastern Australia - Young, J.; Hobday, A.; Campbell, R.; Kloser, Rudy; Bonham, P.; Clementson, L.; Lansdell, M. (Pergamon, 2011)
The surface and sub-surface biological oceanography of tuna fishing grounds within the East Australian Current (EAC) was compared in 2004 with two other fishing areas further offshore. Our aim was to determine whether the biological oceanography of the region could explain the distribution and intensity of pelagic fishery catches inside and outside the EAC at that time. The EAC fishing area was noticeably warmer, less saline and lower in nutrients than waters in the other fishing areas. The EAC waters were dominated by large diatoms, the biomass of which was significantly higher than in the seamount and offshore areas, apparently the result of a cold core eddy beneath the EAC surface filament. Over the seamount and offshore more typical Tasman Sea waters prevailed, although the presence of a relatively deeper oxygen minimum layer over the seamount suggested topographically induced mixing in the area. Notably, sub-surface zooplankton and micronekton biomass was significantly higher around the seamount than in the two other areas. The offshore region was characterised by frontal activity associated with the Tasman front. Micronekton net biomass was generally highest in surface waters in this region. Examination of tuna catch records at that time showed yellowfin tuna (Thunnus albacares) dominated the catches of the EAC, whereas swordfish (Xiphias gladius) and bigeye tuna (Thunnus obesus) were the main species caught offshore. We suggest the yellowfin tuna concentrate in waters that are not only warmer but where prey species are concentrated near the surface. Offshore, deeper living species such as swordfish and bigeye tuna (T. obesus) can take advantage of prey species that are distributed deeper in the water column and along the flanks of the many seamounts in the region, or that are concentrated at fronts associated with the Tasman Front. Although only a snapshot of the region, relatively consistent catch data over time suggests the underlying biological oceanography may persist over longer time periods, particularly during the Austral spring. © 2010.